Non-Motor Symptoms of the Postural Instability and Gait Difficulty Subtype in De Novo Parkinson’s Disease Patients: A Cross-Sectional Study in a Single Center - Ren J (Dove Medical Press, 2020)
Jingru Ren,1 Ping Hua,1 Chenxi Pan,1 Yuqian Li,1 Li Zhang,2 Wenbin Zhang,3 Pingyi Xu,4 Minming Zhang,5 Weiguo Liu1 1Department of Neurology, Affiliated Brain Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 2Department of Geriatrics, Affiliated Brain Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 3Department of Neurosurgery, Affiliated Brain Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 4Department of Neurology, First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 5Department of Radiology, Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, People’s Republic of ChinaCorrespondence: Weiguo LiuDepartment of Neurology, Affiliated Brain Hospital of Nanjing Medical University, 264 Guangzhou Road, Gulou District, Nanjing 210029, People’s Republic of ChinaTel +86-25-82296569Email wgliunbh@sina.comBackground and Purpose: Little is known about non-motor symptoms (NMSs) associated with the postural instability and gait difficulty (PIGD) phenotype, especially in de novo Parkinson’s disease (PD) patients. The aims of this study were to compare NMSs between the tremor dominant (TD) and PIGD phenotypes in de novo PD patients and to determine factors that are associated with the PIGD subtype.Patients and Methods: In a cross-sectional study conducted at our single center, 226 de novo PD patients with a median disease duration of 2 years were recruited. Data, including comprehensive demographics, motor subtypes and NMSs were obtained. Motor subtypes were classified as PIGD and non-PIGD (TD and indeterminate) by Jankovic’s method. NMSs were evaluated by the non-motor symptoms questionnaire (NMSQuest).Results: We identified 73 (32.3%), 34 (15.0%) and 119 (52.7%) patients with TD, intermediate and PIGD subtypes, respectively. Patients with the PIGD subtype had poorer ADL, motor, depression, anxiety, sleep, and non-motor scores compared with those with the TD subtype. In the NMSQuest, the prevalence of cardiovascular, sleep, mood/cognitive and miscellaneous domains was increased in patients with the PIGD subtype compared with patients with the TD subtype. Multivariable forward stepwise logistic regression revealed that the Hamilton Depression Scale (HAMD) [odds ratio (OR), 1.059; 95% confidence interval (CI), 1.016– 1.104, p = 0.007] and pain (OR, 3.175; 95% CI, 1.695– 5.947, p < 0.001) exhibit significant discriminative power in differentiating PIGD and non-PIGD groups.Conclusion: The PIGD group had more severe cardiovascular symptoms, sleep impairments, mood disturbances and pain. We demonstrated for the first time that pain was associated with the PIGD phenotype. Prompt detection and early treatment of NMSs related to the PIGD phenotype may improve patient outcomes.Keywords: de novo Parkinson’s disease, motor subtypes, non-motor symptoms, tremor dominant, postural instability and gait difficulty